TINJAUAN YURIDIS PENYELENGGARAAN PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN - Agus William Frahara Sirait (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
AbstractThis study aims to find out how the implementation of post-transformation PT JAMSOSTEK service into BPJS (Social Security Administering-Agency) Employment. In addition to know how the application of labor protection and service process BPJS (Social Security Administering Agency) Manpower.This research was conducted in Balikpapan City, precisely in BPJS Employment of Balikpapan branch office by taking the relevant data with related parties in this case the organizer of BPJS and related parties and related parties in writing this thesisThis thesis research method using literature research methods (Library Research). The method of research is literature research method by collecting data or reading material that is relevant to the research conducted, while the field research method is research conducted where the author will go directly to the field, in this case the author perform observation or observation to BPJS Employment, And other relevant parties.The results of this study show that after the transformation of PT JAMSOSTEK into BPJS Employment, the government has provided full support for the implementation of BPJS among them by determining the type of health services, set budget and subsidy contributions. The main focus in this thesis is the application of labor protection provided by the Social Security Administering Agency (BPJS) Employment is considered to have provided many improvements in the quality of its services, as well as the addition of programs that provide more benefits to users, both in terms of benefits and tariffs assessed Quite economical.